2015
DOI: 10.1161/jaha.115.002097
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Differences in Catheter Ablation After Hospital Presentation With Symptomatic Atrial Fibrillation

Abstract: BackgroundCatheter ablation is increasingly used for rhythm control in symptomatic atrial fibrillation (AF), but the demographic characteristics of patients undergoing this procedure are unclear.Methods and ResultsWe used data on all admissions at nonfederal acute care hospitals in California, Florida, and New York to identify patients discharged with a primary diagnosis of AF between 2006 and 2011. Our primary outcome was readmission for catheter ablation of AF, identified using validated International Classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…(13,14,2527). Several studies have reported that women have a higher recurrence rate after the ablation procedure(13,14) (25) while other studies have found no significant difference between men and women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(13,14,2527). Several studies have reported that women have a higher recurrence rate after the ablation procedure(13,14) (25) while other studies have found no significant difference between men and women.…”
Section: Discussionmentioning
confidence: 99%
“…(13,14,2527). Several studies have reported that women have a higher recurrence rate after the ablation procedure(13,14) (25) while other studies have found no significant difference between men and women. (26,27) Our study, which is the largest AF ablation study examining procedural outcomes by gender in the United States, found that women were significantly more likely to be re-hospitalized with AF within one-year after an ablation procedure but less likely to undergo cardioversion or repeat ablation.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9]12,13,14 The underlying reason remains to be determined and may be due to physicians' bias or women's reluctance to undergo an invasive procedure as an early treatment option. In this cohort, fewer women received CA although centers were asked to recruit consecutive patients.…”
Section: Referral Patternsmentioning
confidence: 99%
“…Women are underrepresented in most clinical studies on CA for VT, and current guidelines on CA of ventricular arrhythmias do not provide gender specific recommendations . It has been suggested that women are under‐referred for CA for other arrhythmias such as atrial fibrillation . A recent retrospective multicenter study has suggested that women with structural heart disease have higher recurrence rates after CA than men .…”
Section: Introductionmentioning
confidence: 99%